Illuminating Healing: A Comprehensive Review of Blue and Redlight Therapy Applications and Efficacy - Bindod, Harshdeep V.; Hatwar, Pooja R.; Bakal, Dr. Ravindra L.; Dafe, Vedika N. (Asian Journal of Pharmaceutical Research and Development, 2025)
In this study we have assessed the use of blue light (peaking at 415 nm), blue light (approximately 700 nm), and a blue and red light mixture (peaking at 415 and 660 nm) in the treatment of psoriasis, acne vulgaris, diabetes, cancer, actinic keratosis, seasonal affective disorder, and Candida albicans infections. The use of light with wavelengths between 400 and 1100 nm to encourage tissue repair, lower inflammation, and enhance analgesia is known as photobiomodulation (PBM). Red and near-infrared (NIR) light have long been used therapeutically, but new research suggests that blue and green light, among other visible spectrum wavelengths, may also be helpful. The purpose of this review is to assess the research on the possible therapeutic benefits of PBM, with a focus on the effects of red and blue light. This review emphasizes how, depending on the light's wavelength, PBM can have a wide range of effects on the body's various chromophores. The necessity of disclosing exposure and treatment data is still emphasized because doing so will allow for direct comparisons between trials and, ultimately, the identification of PBM's full potential.